Low-Cost Combustion Synthesis, Spectroscopic and Optoelectronic Analysis of Novel Ba2YAlO5:Er3+ Nanomaterials for Competent Illumination Applications. Issue 4 (2nd October 2021) - Sehrawat, Priyanka; Malik, Rajesh Kumar; Punia, Rajesh; Sheoran, Monika; Bedi, Manisha; Dalal, Hina
Abstract : In the current prospective study, novel monoclinic symmetry type Ba2 YAlO5 :Er 3+ nanocrystals with an emanation of vivid greenish light have been manufactured via an ideal, economical and ecological propellant combustion approach. Topographical investigations disclose roughly spherical agglomerated particles of nano-conduct (40-65 nm). Optimized content of the activator (Er 3+ ) has been determined as x = 0.03, after the exigency of luminance quenching directed by the dipole-dipole kind interactions among the nearest Er 3+ ions. The nanocrystals report an intense peak at 549 nm as per 4 S3/2 → 4 I15/2 characteristics transition, excited by 379 nm wavelength, hence proclaims glowing green luminescence. Decay lifetimes of target samples have been found to decline from 3.4556±0.0552 to 1.3063±0.0187 ms, with escalating Er 3+ content. Excellent luminescent profile is reflected in terms of colour parameters like green colour coordinates (0.2630, 0.6205) and 90.79% colour purity, which have been contiguous to standard TV, SD colour green coordinates (0.300, 0.600), European Broadcasting Union (EBU, 0.290, 0.600) and NICHIA LED ( NCSGE17A) green coordinates (0.252, 0. 651). Hence, the overview of present research results insinuate their optimistic candidacy for advanced illuminating appliances like white light-emitting diodes (WLEDs) and other lighting applications. GRAPHICAL ABSTRACT: UF0001